Analisis Stigma Sosial Terhadap Pasien Tuberkulosis Paru di Kecamatan Tilango - Nur Rasdianah; Marsela Idrus Mohamad; Madania Madania; Teti Sutriyati Tuloli; Nur Ain Thomas (Journal of Pharmaceutical and Sciences, 2026)
Tuberculosis (TB) is an infectious disease that remains a global and national health problem. It also leads to social stigma, which may cause patients to be socially excluded, feel ashamed, and delay seeking examination and treatment, thereby becoming a barrier to TB control in the community. This study aims to analyze the level of stigma as well as the factors that are bivariately associated with the level of stigma towards pulmonary tuberculosis patients among respondents in Tilango District. This study employs quantitative design with an analytical cross-sectional approach conducted from January to April 2026 in Tilango Subdistrict. The population consists of 16,390 individuals, and a sample of 376 respondents was selected using the Raosoft calculator (margin of error 5% and confidence level 95%) and the purposive sampling technique. Data are collected using the TB stigma questionnaire (Van Rie) and a knowledge questionnaire regarding TB. Data analysis is conducted using the Chi-Square test. The level of social stigma in the community is predominantly moderate, accounting for 57.7% of the total 376 respondents. The bivariate analysis shows that age, level of education, occupation, history of contact with TB patients, and level of knowledge have a significant association with stigma (p < 0.001). Meanwhile, gender does not show a signifcant association (p = 0.205). This study indicates that social stigma toward pulmonary TB patients among respondents in Tilango Subdistrict remains at a moderate level and is associated with sociodemographic conditions and the level of public knowledge.